General assessment and care of the new patient - Rieke, Klaus; Ulatowski, John A.; Einhäupl, Karl; Hacke, Werner (Neurocritical care, 1994)
Advances in the diagnosis and treatment of neurological disease have recently led to a dramatic increase in neurocritical care units. As most patients with acute life-threatening neurological diseases have systemic disease, the critical care unit facilitates an interdisciplinary approach to patient care that involves neurology, neurosurgery, anesthesiology, and internal medicine. Patients should receive neurocritical care if they have signs of increased intracranial pressure, coma, or neurological disease associated with respiratory or cardiovascular failure. Other patients who may benefit from neurocritical care include those with subarachnoid hemorrhage (all grades), space-occupying hemorrhage or stroke, meningitis, encephalitis, status epilepticus, and progressive muscular weakness (especially involving the respiratory muscles; Table 1). Patients receiving thrombolytic therapy and plasmapheresis or those undergoing interventional neuroradiological procedures may also benefit from neurocritical care (high- or low-acuity monitoring).
Gesehen am 03.06.2025